Architecture and cellular composition of focal cortical dysplasia type II: qualitative review of histological studies - Castaño-Martín, Reyes; Metais, Alice; Ciura, Sorana; Blauwblomme, Thomas (Frontiers in Cellular Neuroscience, 2025)
Focal cortical dysplasia (FCD) is a malformation of cortical development strongly associated with drug-resistant epilepsy, particularly in children but also observed in adults. FCD type II is specifically characterised by cortical disorganisation and the presence of abnormal cells. This condition has been widely linked to hyperactivation of the mTOR signalling pathway, secondary to somatic mutations. After five decades of research, the comprehensive understanding of FCD architecture remains incomplete, with significant variability across studies, influenced by differences in tissue samples, cohort characteristics, and experimental protocols. This review aims to synthesise current knowledge on FCD architecture to clarify how the cerebral cortex is altered in FCD. We particularly focus on the hallmarks of FCD: cortical dislamination, balloon cells, and dysmorphic neurons. Additionally, we explore recent insights into the composition of cortical neuronal populations, emphasising the role of inhibitory interneuron populations, which have gained attention following discoveries regarding the involvement of GABAergic signalling in epileptogenesis. Overall, our review highlights key considerations for future single-cell and spatial studies aimed at minimising sampling bias.